Les opérations d’assurance et de réassurance dans les pays en voie de développement : étude du secrétariat de la CNUCED - Outreville, J.-François (Assurances)

(untitled) (HEC Montréal, 1988)
Every two years, the United Nations Conference on Commerce and Development publishes a study on recent events in the field of insurance and reinsurance in developing countries. This year, it has added a study of statistical data on insurance and reinsurance operations which is available on demand. Following is a summary of these statistical data.